Potensi Ekonomi dan Manfaat Hidrologis Pertambangan Pasir Sungai Sadang di Pinrang Sulawesi Selatan - Arsyad Arsyad; Didi Rukmana; Darmawan Salman; Ilham Alimuddin (Jurnal Ilmu Alam dan Lingkungan, 2020)
Sand is a material needed for various purposes such as construction materials and backfill materials so that the need for sand continues to increase. The economic potential in the form of increasing sand demand has triggered increased sand mining activities in the Sadang River in Pinrang Regency. The research took place between September and November 2019 which aimed to determine the economic potential and hydrological benefits of the Sadang River sand mining in Pinrang Regency. The research area covers three districts included in the Sadang River sand mining area of Pinrang Regency namely Patampanua, Duampanua and Cempa Districts. A field survey was conducted to find out the amount of production volume, production costs, mining and transportation activities. The results showed that the Sadang River sand mining has considerable economic potential. In addition to direct economic benefits, it also provides indirect economic benefits for the community around the mining area. If the river sand mining has been deemed damaging to the environment and disrupting the function of the river, then the passive river of Sadang River shows the opposite fact, namely that the Sadang River sand mining can help restore the hydrological function of the Sadang River to prevent siltation of the Sadang River due to sedimentation so as not to cause overflow and floods that can damage residents' settlements and agricultural land in three districts.